PENENTUAN WAKTU FERMENTASI OPTIMUM PRODUKSI XILANASE DARI Trichoderma viride MENGGUNAKAN SUBSTRAT KULIT PISANG DAN KULIT MELON DENGAN FERMENTASI SEMI PADAT - Mahdi, Chanif; Sutisno, Sutrisno; Hastari, Ayunda Antika (Jurnal Ilmu Kimia Universitas Brawijaya, 2014)
Trichoderma viride is a type of mold that most available in land and has several more advantages when compared with other types of soil fungi . This reseach is aimed to know optimum fermentation periode and type of optimum substrate in xylanase production from Trichoderma viride by semi solid fermentation. Optimum fermentation periode and type of optimum substrate determined by measure of enzyme activity and protein content in various fermentation times ( 0 , 12 , 24 , 36 , 48 , 60 , 72 . 84 , and 96 hours ) using melon peels and banana. Xylanase is type of enzyme that able to hydrolyze hemicellulose ( xylan ) into xylose . Determination of enzyme activity begins with a solution of pure xylan in 1 % concentration at pH 5 and a temperature of 60 ° C (optimum conditions). Determination of enzyme activity is determined by measure xilosa in enzimatis reaction with spectrofotometri methode and DNS regen. Protein content determined by spetrophotometry methode with biuret reagen. The results fermentation 60 hour showed optimum activity in the melon peel and banana peel, that is (20,16±8,17) unit dan (19,42±8,00) unit (P<0,01) and protein content (16,86±8,23) mg/mL dan (16,88±4,32) mg/mL (P<0,01).